Abnormally high expression of D1-like dopamine receptors on lupus CD4+ T cells promotes Tfh cell differentiation - Wu, Fengxi; Xiang, Zhongyuan; He, Zhenghao; Yi, Ping; Yang, Ming; Wu, Haijing; Hu, Min (Lupus science & medicine, 2023)
ObjectiveSLE is a chronic autoimmune disease that places a great burden on human society. T follicular helper (Tfh) cells play a critical role in the pathological process of SLE. Therefore, elucidating the mechanism of Tfh cell differentiation will contribute to SLE treatment. Dopamine receptors (DRDs) are members of the family of G protein-coupled receptors and are primarily divided into D1-like and D2-like receptors. Previous studies have found that DRDs can regulate differentiation of immune cells. However, there is currently a lack of research on DRDs and Tfh cells. We here explore the relationship between DRDs and Tfh cells, and analyse the relationship between DRD expression on Tfh cells and the course of SLE.MethodsWe first detected plasma catecholamine concentrations in patients with SLE and healthy controls by mass spectrometry, followed by reverse transcription-quantitative PCR (RT-qPCR) to detect DRD messenger RNA (mRNA) expression in peripheral blood mononuclear cells (PBMCs) and CD4+ T cells, and flow cytometry to detect DRD expression in Tfh cells. Finally, in vitro experiments and RNA sequencing (RNA-seq) were used to explore the possible pathway by which DRDs regulate Tfh cell differentiation.ResultsThe plasma dopamine concentration in patients with SLE was significantly increased, and abnormal mRNA expression of DRDs was observed in both PBMCs and CD4+ T cells. The results of flow cytometry showed that D1-like receptors were highly expressed in Tfh cells of patients with SLE and associated with disease activity. In vitro induction experiments showed that differentiation of naïve T cells into Tfh cells was accompanied by an increase in D1-like receptor expression. RNA-seq and RT-qPCR results indicate that D1-like receptors might promote Tfh cell differentiation through the Phosphatidylinositol3-kinase (PI3K)/protein kinase B (AKT)/Forkhead box protein O1 (FOXO1)/Kruppel-like factor 2 (Klf2) pathway.ConclusionTfh cells in patients with SLE highly express D1-like receptors, which correlate with disease activity. D1-like receptors may promote Tfh cell differentiation through the PI3K/AKT/FOXO1/Klf2 pathway.